2014
DOI: 10.1016/j.physleta.2014.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the spin–orbit coupling on the vacancy-induced magnetism on the honeycomb lattice

Abstract: The local magnetism induced by vacancies in the presence of the spin-orbital interaction is investigated based on the half-filled Kane-Mele-Hubbard model on the honeycomb lattice. Using the self-consistent mean-field theory, we find that the spin-orbital coupling will enhance the localization of the spin moments near a single vacancy. We further study the magnetic structures along the zigzag edges formed by a chain of vacancies. We find that the spin-orbital coupling tends to suppress the counter-polarized fer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…There is a local antiferromagnetic moment around the impurity site. The resulting antiferromagnetic pattern has been observed in other theoretical studies of the vacancy defect in graphene using mean-field 9,46 or density functional theory. 10 The 120 • rotation symmetry is not exactly found in our solution since both the cluster and the supercluster do not have that symmetry.…”
Section: I-cdmft Resultssupporting
confidence: 62%
“…There is a local antiferromagnetic moment around the impurity site. The resulting antiferromagnetic pattern has been observed in other theoretical studies of the vacancy defect in graphene using mean-field 9,46 or density functional theory. 10 The 120 • rotation symmetry is not exactly found in our solution since both the cluster and the supercluster do not have that symmetry.…”
Section: I-cdmft Resultssupporting
confidence: 62%
“…The SOC also contributes to suppress the edge magnetism in the zigzag graphene nanoribbon [21]. Leong et al, [22] revealed the enhancement of localized spin moments near a single vacancy under affecting the SOC. The change of topological edge states and spontaneous magnetic moment properties of zigzag graphene nanoribbons were reported recently [23].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the strong correlation effects may be introduced by suppression the itinerancy of p z electrons. Following this idea, several schemes to trigger the magnetism in graphene nanostructures were proposed by breaking the perfect sp 2 network and generating the local imbalance of bipartite sublattice of graphene [7], including the atomic vacancies [8][9][10], adsorbing adatoms [11], sp 3 functionalization [12], substitutional doping [13][14][15], and the zigzag edges in the nanoflakes such as the nanoribbons or nanoislands [16][17][18]. For example, the atomic vacancies and chemisorbed hydrogen atom on graphene can induce the unusually several-nanometers-distant spin texture [11], the sulfur-and nitrogen-doped graphene can produce the strong room-temperature ferromagnetism [19][20][21][22], and the zigzag edges can generate the strong ferromagnetism along the edges due to the flat band emerging at the edges [23][24][25].…”
Section: Introductionmentioning
confidence: 99%